Impact of growth temperature on exopolysaccharide production and probiotic properties of Lactobacillus paracasei strains isolated from kefir grains - Bengoa, Ana Agustina (2018)
EPS-producing LAB are widely used in the dairy industry since these polymers improve the viscosity and texture of the products. Besides, EPS might be responsible for several health benefits attributed to probiotic strains. However, growth conditions (culture media, temperature, pH) could modify EPS production affecting both technological and probiotic properties. In this work, the influence of growth temperature on EPS production was evaluated, as well as the consequences of these changes in the probiotic properties of the strains. All Lactobacillus paracasei strains used in the study showed changes in EPS production caused by growth temperature, evidenced by the appearance of a high molecular weight fraction and an increment in the total amount of produced EPS at lower temperature. Nevertheless, these changes do not affect the probiotic properties of the strains; L. paracasei strains grown at 20 °C, 30 °C and 37 °C were able to survive in simulated gastrointestinal conditions, to adhere to Caco-2 cells after that treatment and to modulate the epithelial innate immune response. The results suggest that selected L. paracasei strains are new probiotic candidates that can be used in a wide range of functional foods in which temperature could be used as a tool to improve the technological properties of the product.